Habitual food consumption of the Belgian population in 2014-2015 and adherence to food-based dietary guidelines. - Sarah Bel; Karin De Ridder; Thérésa Lebacq; Cloë Ost; Teppers, Eveline; Koenraad Cuypers; Jean Tafforeau (Arch Public Health, 2019)
Background: Between 2014 and 2015 a second National Food Consumption Survey was conducted in Belgium in order to evaluate the habitual food consumption in the general Belgian population and to compare it with food-based dietary guidelines (FBDG) and results of the 2004 Food Consumption Survey. Methods: A representative sample of the Belgian population was randomly selected from the National Population Register following a multistage stratified sampling procedure. Information on dietary intake was collected from 3146 subjects between 3 and 64 year old through two non-consecutive 24-hour dietary recalls using GloboDiet®. In addition, a self-administered food frequency questionnaire was completed. The distribution of habitual food consumptions and proportion of persons who did not meet the recommendations were estimated with SPADE. Results: For most of food groups analysed, the habitual consumption did not comply with FBDG. The consumption of nutrient-poor and energy-dense foods (e.g. alcohol, soft drinks and snacks) was excessive (35% of total energy intake), while the consumption of most other food groups was below the minimum recommended. A large majority of the population had an inadequate consumption of dairy products (98%), vegetables (95%), fruit (91%), potatoes, rice and pasta (88%) bread and cereals (83%) and water and sugar-free drinks (73%). Males had higher consumption of most food groups than females, thereby complying more often with FBDG. For all food groups, except dairy products and fruit, the consumption increased with age. The proportion of individuals meeting FBDG was the highest among young children (3-5 years) and the worst among adolescents aged 14-17 years old. Habitual consumption remained stable between 2004 and 2014 in the population aged 15-64 years old for all food groups except for increased consumption of water and sugar-free drinks (1180 to 1289 g/d) and decreased consumption of spreadable and cooking fat (27 to 19 g/d), red meat (34 to 25 g/d) and bread and cereals (173 to 142 g/d). Conclusions: The habitual food consumption of the Belgian population (3-64 years) in 2014-2015 deviates largely from FBDG, particularly among adolescents aged between 14 and 17 years old. Few improvements were observed between 2004 and 2014 in the population between 15 and 64 years old. Further efforts are therefore necessary to improve dietary habits in Belgium, in order to prevent and reduce diet-related diseases.
Keywords: 2014-2015; Adolescents; adults; CHILDREN; food consumption survey